(3efgGL GdWGdHjf ddeHJOjf ef GdeQjOjf GdUGObjfs - (3LGeY GdCej GdSYOj GdTGaYj GdaJhMjs; (3eMjj GdOjf Hf GdYQHj,J (B638 (3g` s ((3YHOGdoeMSf Hf eMeO GdTHgjSj s)
(3ChdgG (B:s
(3GdMeO ddg GdehUha HUaGJ GdceGd GdeYQha HYehe GdaVd hNUhU GdgHGJ GdeJcde HcdGe bOje bHd Ndb GdMQha hGdCUhGJ s
(3BNQgG (B:s
(3hGdoeNGdaGJ hGdYbdGJ hebGWYI Je TQM eG JbOe ef GdQSGdI GdePchQI aj ChGFd gPG GdcJGH GdeHGQc HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3QSGdI GdCfhGQ deMj GHf GdYQHi (B"(3GfXQ cTa GdXfhf L (B1 (3U`(B849s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJUha hGdBOGH GdTQYjIs